Lipid-based nutrient supplement increases the birth size of infants of primiparous women in Ghana - Adu-Afarwuah, S.; Lartey, A.; Okronipa, H.; Ashorn, P.; Zeilani, M.; Peerson, J.M.; Arimond, M.; Vosti, S.; Dewey, K.G. (American Journal of Clinical Nutrition, 2015)
Background: The International Lipid-Based Nutrient Supplements Project developed a small-quantity (20 g/d) lipid-based nutrient supplement (LNS) for pregnant and lactating women. Objective: We evaluated the effects of prenatal LNS supplementation on fetal growth. Design: In a community-based, partially double-blind, individually randomized controlled trial, 1320 women ≤20 wk pregnant received 60 mg Fe/400 mg folic acid (IFA), or 1-2 Recommended Dietary Allowances of 18 micronutrients, including 20 mg Fe (MMN), or LNS with the same micronutrients as the MMN group, plus 4 minerals and macronutrients contributing 118 kcal (LNS) daily until delivery. Fetal growth was compared across groups by using intention- to-treat analysis. The primary outcome was birth length. Results: This analysis included 1057 women (IFA = 349, MMN = 354, LNS = 354). Groups did not differ significantly in mean birth length, length-for-age z score (LAZ), head circumference, or percentage low birth length but differed in mean birth weight (P = 0.044), weight-for-age z score (WAZ; P = 0.046), and BMI-forage z score (BMIZ; P = 0.040), with a trend toward differences in low birth weight (P = 0.069). In pairwise comparisons, the LNS group had greater mean birth weight (+85 g; P = 0.040), WAZ (+0.19; P = 0.045), and BMIZ (+0.21; P = 0.035) and a lower risk of low birth weight (RR: 0.61, 95% CI: 0.39, 0.96; P = 0.032) than did the IFA group. The other group differences were not significant. The effect of intervention was modified by mother's parity, age, height, baseline hemoglobin, household food insecurity, and child sex, with parity being the most consistent modifier. Among primiparous women (IFA = 131; MMN = 110; LNS = 128), the LNS group had greater mean birth length (+0.91 cm; P = 0.001), LAZ (+0.47; P = 0.001), weight (+237 g; P < 0.001), WAZ (+0.56; P < 0.001), BMIZ (+0.52; P < 0.001), head circumference (0.50 cm; P = 0.017), and head circumference-for-age z score (+0.40; P = 0.022) than did the IFA group; similar differences were found when comparing the LNS and MMN groups among primiparous women, and no group differences were found among multiparous women. Conclusion: Prenatal LNS supplementation can improve fetal growth among vulnerable women in Ghana, particularly primiparous women. © 2015 American Society for Nutrition.
Keywords: Child nutrition; Fetal growth restriction; Lipid-based nutrient supplements; Maternal nutrition; Multiple micronutrients; Pregnancy outcome; Prenatal supplementation